Economic analysis of four crop rotation systems for wheat, over ten years, in Passo Fundo, RS - dos Santos, Henrique Pereira; Ignaczak, João Carlos; Lhamby, Julio Cesar Barreneche; Ambrosi, Ivo (Pesquisa Agropecuaria Brasileira, 1995)
From 1980 to 1989, at the Centro Nacional de Pesquisa de Trigo, in Passo Fundo, RS, Brazil, the effects of crop rotation systems on wheat were assessed. Four rotation systems for wheat were studied: system I (wheat/soybean); system II (wheat/soybean, rapeseed/soybean, barley/soybean, legume/corn); system III (wheat/soybean, legume/legume and legume/corn, from 1980 to 1983, and wheat/soybean, white oats/soybean and legume/corn, from 1984 to 1989); and system IV (wheat/soybean, rapeseed/soybean, flax/soybean and legume/corn). A randomized complete block design, with four replications and plots with 120 m2 was used. Economic analysis on that period is presented in this paper. The mean net retum of ten years of system II (US 302.22) was higher than that of system I (US 180.73). On the other hand, system IV (US 293.95) was superior to system III (US 186.56) and similar to system I.